Spatial distribution of bowal and differences in physicochemical characteristics between bowal and woodland areas in Benin, West Africa - PADONOU, Elie Antoine; BACHMANN, Y.; GLELE KAKAÏ, A. ROMAIN LUCAS; Mette Lykke, Anne; SINSIN, Brice (My University, 2015)
Bowal, degraded land is ferricrete exposure due to soil surface erosion. This study aims at assessing the spatial distribution of bowé in Benin and the physical chemical differences between ferricretes exposed on bowé and soil of adjacent woodlands. Bowé sites were identified during field exploration in Benin and their geographic coordinates were stored. Soil samples were taken on the bowé sites and nearby woodland. Mann-Whitney test was applied to analyze the different physicochemical characteristics of bowé and woodland sites. The results show that bowé were directly related to ferruginous soils and rainfall regime. Bowé showed significantly lower values of electrical conductivity, organic matter, extractable phosphorus, silt and total nitrogen than woodland soils, while its potassium exchangeability was higher. Bowé can be expected wherever ferruginous soil is observed in unimodal rainfall regime condition. The disaggregation of bowé may improve the soil physicochemical characteristics and sustain the regrowth of forest if the climate becomes more humid.
Keywords: Bowal; bowé; Ferruginous soil; Physicochemical soil characteristics; Phytogeographical district; Benin